THE EFFECT WORD OF MOUTH, PRODUCT QUALITY AND PRICE ON PURCHASE DECISIONS AT MIE GACOAN IN SIDOARJO - Cindy Debby Mayank Sary; Komalasari, Dewi (PT. Antis International Publisher, 2025)
Objective: The research aims to determine Word of mouth, Product quality, and Price on Purchasing decisions for Gacoan noodles in Sidoarjo. Method: By using a quantitative approach, this approach can be used to test theory objectively by looking at the relationship between variabels. Sampling was taken using a no-probability sampling technique using a purposive a sampling method, the total sample was 100 Gacoan noodles consumers in all Sidoarjo district oulets. The data analysis technique uses multiple linear regression analysis with the SPSS V25 program. Results: The research results include; Word of Mouth influences Purchasing Decisions, Product quality influences Purchasing Decisions, Price influences Purchasing Decisions. Novelty: This research provides new insights into consumer purchasing behavior in the local culinary industry, specifically targeting Gacoan noodles consumers in Sidoarjo, which has not been widely studied in previous literature.